Effects of Combination Native and Modified Starch on The Rheological and Sensory Characteristics of Ice Cream - Ng, Yih Fang; Faridah Kormin; Shaharuddin Kormin (Enhanced Knowledge in Sciences and Technology, 2022)
Ice cream is a good source of proteins, carbohydrates, fats, vitamins and minerals. Even though ice cream is rich in proteins, it has been considered as a high-calorie junk food with high fats and sugar content. This is because of the high content of fat and sugar in ice cream to enrich the richness and creaminess of taste and texture. The taste and texture of ice cream is deteriorated by the recrystallization due to fluctuating temperature during handling, storage and distribution. In the recrystallization, the ice crystal size increases, thus, causing the ice cream to become harder and this unpleasant texture reduces the consumers’ acceptance. The combination of native and modified starch was used to overcome the recrystallization and improved the limitation of native starch due to its limited functionality. The physicochemical properties such as overrun and melting rate, rheological properties and nutritional analysis were determined. From the result, ice cream with guar gum only has the highest overrun which is about 97.8% and ice cream without starches has the lowest overrun which is about 48.1%. Ice cream with maltodextrin only has the highest melting rate which is about 0.389±0.010g/min and ice cream with 1:1 ratio of guar gum and maltodextrin has the lowest melting rate which is 0.278±0.025g/min. The ice cream with higher concentration of guar gum is more stable to the temperature fluctuation and less crystallization is formed. The ice cream without starch has the highest viscosity which is 2.667±0.711Pa.s and the ice cream with maltodextrin only has the lowest viscosity which is 0.058±0.015Pa.s. The ice cream with a ratio 1:1 guar gum and maltodextrin has the highest overall sensory acceptance which received 7.093±1.275 points. Based on the results obtained, the ratio of 1:1 guar gum and maltodextrin is the most optimal in ice cream. Ice cream with a ratio of 1:1 guar gum and maltodextrin has the lowest melting rate, highest overall sensory acceptance and moderate viscosity. The calories, total carbohydrates, protein and total sugars content of the ice cream with a ratio of 1:1 guar gum and maltodextrin is lower than commercial brand A and B. Besides that, the total fats of the ice cream with ratio of 1:1 guar gum and maltodextrin is higher than commercial brand A but lower than commercial brand B.